Profit Analysis Of Karuna Cell Pulsa Agent In Karangrayung, Grobogan - Sri Martono; Myra Heltyani (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2021)
Background: Profitability ratio analysis is a ratio used to measure the company's ability to generate profits from sales. Therefore, Karuna Cell pulsa agents are required to be able to assess the condition and development of the store through ratio analysis of financial statements in order to maintain the existence of the store and be able to increase business growth amid increasingly rapid economic growth and increasingly fierce business competition. Purpose: The purpose of this study was to determine the gross profit margin ratio at Karuna Cell credit agents. This is analyzed in terms of profitability and analysis in terms of financial statements. Financial statement ratio analysis commonly used is liquidity ratio analysis or working capital ratio, solvency ratio analysis, and profitability ratio analysis. Methods: The research method used is collecting data from primary data sources and secondary data sources. Primary data sources were obtained from existing data in the field through interviews and observations at the Karuna Cell pulsa agent, while secondary data sources were obtained from literature studies. Results: Gross Profit Margin at Karuna Cell credit agents is 8%, Net Profit Margin at Karuna Cell credit agents is 7.33%, Return on assets at Karuna Cell credit agents is 24%. Conclusion: It can be concluded that, if gross profit margin is high, so it would increase the net profit margin ratio.